Pengaruh Motivasi Belajar dan Kecerdasan Numerik Siswa terhadap Prestasi Belajar Matematika - Tuty Kurniawaty Saragih (Universitas Indraprasta PGRI Jakarta, 2019)
This research was experiment used survey method using Korelasional analysis techniques. Results of the study explained that the motivation of learning provide positive influence toward learning math achievements marked by the acquisition of koefesien determination R2 = 0.483 of significance that 48.3% of achievement can learn math variable explained by the motivation to learn. Numerical intelligence provide positive influence toward learning math achievements marked by the acquisition of the coefficient determination R2 of 0.616 has significance that 61.6% achievement learning math can be explained by the variable numeric Intelligence students. Learning motivation and numerical intelligence together gave a positive influence towards the achievements of the students learn math which is characterized by the coefficient of determination (R) 2 of 0.824 82.4% meaning the accomplishment of learning math can described by the learning motivation variables and numerical intelligence together